Hubungan Indeks Prestasi Kumulatif Mahasiswa Dengan Keterampilan Mahasiswa Dalam Melakukan Tindakan Heacting Di Stikes Ngudia Husada Madura - Nisfil Mufida (NHM PRESS, 2018)
Emesis is the most common complaints found in the 1st trimester pregnant women, if allowed to continue then allow the emergence of problems in pregnancy such as hyperemesis, anemia aims perdarahan.Penelitian even know emesis gravidarum relationship with the incidence of anemia in pregnant women first trimester.This type of research is analytic survey with cross sectional design. Emesis gravidarum independent variables and the dependent variable is used anemia.Populasi is first trimester pregnant women as many as 34 people, with the technique of sampling probabilitysampling taking a simple random sample of 31 people sampling.Besar. Collecting data using guided interviews and examination of hemoglobin levels with Sahli method. Results obtained data processing first trimester pregnant women who experienced emesis by 83.9%, 70.9% mild anemia. So that mothers who experienced emesis with mild anemia of 80.8%. Chi-Square test results obtained probability value is smaller than the degree of error (0.000 <0.05) so that Ha is accepted Ho is rejected, it can be inferred the existence of a relationship between emesis gravidarum with anemia in pregnant women first trimester. To prevent and deal with any incidence of emesis in pregnant women it does adequately handling to prevent anemia arising from the signs and symptoms of anemia is present emesis.Bila periodically anemia screening, counseling, information and education about anemia and emesis in pregnant women